DIAGENESIS ANALYSIST AND POROSITY DEVELOPMENT OF RAJAMANDALA CARBONATE THROUGHOUT THIN SECTION AND STABLE ISOTOPE APPROACHES: A CASE STUDY FROM CIKAMUNING AREA, WEST JAVA-INDONESIA - ALAM PERDANA, LISNANDA
Rajamandala carbonate rock (Oligocene-Miocene) cropped out in West Java with northeast-southwest trend. Petrography detail analysis have been conducted using polarization and cathodoluminescence microscope, integration with isotope data is the main control for synthesizing diagenesis evolution. This research using three shallow well which are ITB_URC-1, ITB_URC-2, ITB_URC-3 (90-151m) combine with surface data. Carbonate cement analysis showed us domination of blocky, isopach cement with aggrading characteristic. Main composition of cement is Fe-calcite with dolomitization in several places. Cathodoluminescence analysis reveal that dolomitization occur three times with saddle, planar and polimodal texture with inequally distribution. Stable isotope value of ?18 range from -2o/000 until -8o/000 and ?13C range from 2 o/000 until -2o/000 indicate that carbonate rock diagenesis have been through burial phase with highly develop in cementation process connected with water formation and meteoric water. This research confirmed that porosity modification in Cikamuning area controlled by five diagenesis zone which are marine, meteoric phreatic, mixing, burial with meteoric phreatic zone as main factor controlling porosity. Porosity value in the well have a small percentation (<10%) and dominated with dissolution. Dolomitization just localized and not significant for enhancing porosity. The result of the whole analysis reveal that diagenesis in subsurface can be modelled by surface data with erasing surfacial process.